Real‐World Treatment Patterns and Clinical Outcomes in Advanced Gastrointestinal Neuroendocrine Tumors (GI NET): A Multicenter Retrospective Chart Review Study. (3rd January 2019) - Kulke, Matthew H.; Benson, Al B.; Dasari, Arvind; Huynh, Lynn; Cai, Beilei; Totev, Todor; Roesner, Nina; Duh, Mei Sheng; Neary, Maureen P.; Maurer, Victoria E.; Shih, Brandon E.; Dagohoy, Cecile G.; et al.
Abstract: Background: We assessed treatment patterns and outcomes of patients with advanced gastrointestinal (GI) neuroendocrine tumors (NET) at four large tertiary referral centers in the U.S. Patients and Methods: We performed a retrospective chart review of patients aged ≥18 years at advanced GI NET diagnosis, treated between July 2011 and December 2014. Index date was the histologically confirmed diagnosis date of locally advanced/metastatic GI NET. Data included baseline characteristics, treatment patterns, progression, death, and GI NET‐related health care resource utilization from index date through last contact or death. Time‐to‐event analyses, including treatment discontinuation, progression, and overall survival (OS), were performed using Kaplan‐Meier analysis. Results: We identified 273 patients; 156 (57%) had primary ileum NET, and 174 (64%) had functional NET. First‐line treatments included somatostatin analog (SSA) alone (89%) or in combination (2%), liver‐directed therapy (LDT; 8%), and cytotoxic chemotherapy or interferon (2%). One hundred fifty‐five patients continued with second‐line therapy, including SSA alone (17%) or in combination (75%, with 3% combined with peptide receptor radionuclide therapy), LDT (4%), and other treatments (3%). Median time (months) to first‐line discontinuation was 154.0 for SSAs and 3.8 for cytotoxic chemotherapy. Overall median time to investigator‐assessed progression following treatment initiation was 30.3 months. Median OS (months) following first‐line initiation was 151.8 for all patients and 178.9 for first‐line SSA. Conclusion: Our study illustrates the common use of SSAs in both first‐line and subsequent treatment of patients with GI NETs, as well as the relatively long survival durations and multiple additional treatments received by patients with this condition. Treatment pattern assessment at later times, following approval of newer treatments, is warranted. Abstract : To better understand treatment patterns and outcomes for patients with advanced gastrointestinal neuroendocrine tumors, a retrospective patient chart review was performed and treatment patterns were assessed for patients at four major tertiary care centers in the U.S. Results of the study are reported here.